The Effect of The Numbered Head Together Learning Model on Student Achievement in Science Subjects Style Class IV SDN 3 Sukamanah - Vivi Erpianti; Meiliana Nurfitriani; M Fahmi Nugraha (Jurnal Sekolah Dasar, 2021)
Science learning must be interpreted as an activity that is observational, experimental and predictive, so that students can understand science concepts appropriately and can be verified. In science learning in grade IV SDN 3 Sukamanah there are several obstacles in learning style material, namely the lack of supporting facilities when science subjects take place such as learning media and practical tools, style material for fourth grade students is still unfamiliar / new to learn like the style what the student means is the selfie or swimming style so that the teacher also requires a lot of time and must prepare adequate support and the learning process carried out by the teacher only uses the lecture learning model, so that learning achievement in science subjects does not achieve the learning objectives which are expected. Based on these problems, the researchers applied the Numbered Head Together learning model to determine the effect on student achievement in science subjects class IV style material of SDN 3 Sukamanah. The research method used in this study is an experimental research method with a quasi-experimental design in the form of One-Group Pretest-Posttest. The research was conducted at SDN 3 Sukamanah with a population of sixteen people.